Clozapine-induced intestinal occlusion: a serious side effect - Pelizza, L.; De luca, P.; La Pesa, et al., M. (Acta Biomedica Atenei Parmensis, 2007)
Aim of this article is to describe the first italian case reported in literature of a clozapine-induced intestinal occlusion with previous severe constipation in a 45-year-old male patient who had been treated with daily clozapine for 5 months because of treatment-resistant residual schizophrenia.When conservative treatment (intravenous fluids, fleet enema and rectal washout) was used and clozapine therapy was decreased, gastrointestinal symptoms rapidly improved and the patient had regular bowel motions within a week. Preventive measures (high-fiber diet, adequate fluid intake, stool softeners and exercise) was also used to ensure that clozapine therapy could be safely continued. Although constipation is a common and usually benign side effect of treatment with clozapine, this case-report highlights the consequences of undertreated and unrecognized marked constipation progressing to severe bowel obstruction (a complication which deserves more attention because it can lead to hospitalization and might be potentially fatal).